Screening Enteric Bacteria with Inhibitory Effects Against Pathogenic Clostridium difficile and Its Spore - Chonticha Romyasamit (Prince of Songkla University, 2021)
Thesis (Ph.D., Biomedical Sciences)--Prince of Songkla University, 2019